Catgut embedding in acupoints combined with repetitive transcranial magnetic stimulation for the treatment of postmenopausal osteoporosis: study protocol for a randomized clinical trial - Qiu, Jingjing; Xu, JiaZi; Cai, Yingyue; Li, Minghong; Peng, Yingsin; Xu, Yunxiang; Chen, Guizhen (Frontiers in Neurology, 2024)
Background To date, the clinical modulation for bone metabolism based on the neuro-bone mass regulation theory is still not popular. The stimulation of nerve systems to explore novel treatments for Postmenopausal osteoporosis (PMOP) is urgent and significant. Preliminary research results suggested that changes brain function and structure may play a crucial role in bone metabolism with PMOP. Thus, we set up a clinical trial to investigate the effect of the combination of repetitive transcranial magnetic stimulation (rTMS) and catgut embedding in acupoints (CEA) for PMOP and to elucidate the central mechanism of this neural stimulation in regulating bone metabolism. Method This trial is a prospective and randomized controlled trial. 96 PMOP participants will be randomized in a 1:1:1 ratio into a CEA group, an rTMS group, or a combined one. Participants will receive CEA, rTMS, or combined therapy for 3 months with 8 weeks of follow-up. The primary outcomes will be the changes in Bone Mineral Density scores, total efficiency of Chinese Medicine Symptoms before and after treatment. Secondary outcomes include the McGill Pain Questionnaire Short-Form, Osteoporosis Symptom Score, Mini-Mental State Examination, and Beck Depression Inventory-II. The leptin, leptin receptor, and norepinephrine levels of peripheral blood must be measured before and after treatment. Adverse events that occur during the trial will be recorded. Discussion CEA achieves brain-bone mass regulation through the bottom-up way of peripheral-central while rTMS achieves it through the top-down stimulation of central-peripheral. CEA combined with rTMS can stimulate the peripheral-central at the same time and promote peripheral bone mass formation. The combination of CEA and rTMS may play a coordinating, synergistic, and side-effect-reducing role, which is of great clinical significance in exploring better treatment options for PMOP. Clinical trial registration: https://www.chictr.org.cn/, identifier ChiCTR2300073863.